A Class of One-Sixth Hybrid Methods for Direct Solution of Third Order Ordinary Differential Equations - Taiwo, Oluwasayo Esther; Ogunniran, Muideen O. (Mikailalsys Journal of Mathematics and Statistics, 2025)
In this paper, a class of Hybrid methods for solving third order ordinary differential equations directly is developed. These methods were derived using interpolation and collocation techniques. The methods were analyzed based on the properties of linear multistep methods and were found to be zero-stable, consistent and convergent with good region of absolute stability. The proposed methods were implemented on higher order ordinary differential initial value problems. The superirity of the proposed methods over existing ones was demonstrated through some numerical examples.